Las traducciones húngaras del romancero gitano de Federico García Lorca - Katona, Eszter (Acta Hispanica, 2009)
Federico García Lorca’s first volume of poems translated to Hungarian was The Gipsy Ballads, which was published in 1947 in two independent editions (Cserépfalvi and Lux Publishing Companies) at the same time. Readers got acquainted with Lorcas’s lovely romances through the translations of Ervin Gyertyán and László András. In 1963 a new edition enriched Lorca’s image in Hungarian, this time Európa Publishing Company issued the The Gipsy Ballads cycle within a volume along with other poets’ works, but this time the poems were translated to Hungarian by László Nagy. The aim of this paper was to compare the three different Hungarian translations. Obviously, within the limits of this article it was impossible to compare all the ballads, therefore I have selected three poems (Romance de la luna, luna; La monja gitana; Precios y el aire) of the volume, in order to present through differences/similarities of syntactic, semantic and poetical aspects the importance of the translators’ valuable work in presenting Lorca’s duende in Hungarian language.